Productivity of Butterfly Pea (Clitoria ternatea L.) Influenced by Urea Fertilizer Rates and Harvest Ages in Kulon Progo, Yogyakarta, Indonesia - Wardi Wardi; Nafiatul Umami; Asih Kurniawati; Bambang Suhartanto; Chusnul Hanim; Zen Adyatama (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2023)
Butterfly pea (Clitoria ternatea L.) is leguminous species that contain high nutritional values. This study aimed to determine the effect of the rate of urea fertilizer and harvest age on the productivity of butterfly pea forage. This research used a split-plot design consisting of urea rates (0, 100, and 200 kg/ha) and harvest ages (30, 45, and 60 days after planting or DAP) with three replications. The variables observed were morphological growth (plant height, stem diameter, number of leaves, and number of branches), and productivity of forage biomass (fresh weight, dry weight, and crude protein). The data obtained were analyzed using ANOVA and the means were separated by using Duncan's Multiple Range Test (DMRT). The interaction between fertilizer rates and harvest ages was shown (p<0.05) on stem diameter, number of leaves, number of branches, and fresh weight of butterfly pea. The increased rates of fertilizer and harvest ages significantly affected (p<0.05) in the morphological growth and productivity of butterfly pea biomass. The application of urea fertilizer increased plant length from 10.59 to 17.16%, stem diameter from 12.12 to 24.24%, number of leaves from 15.40 to 28.20%, and number of branches from 81.82 to 190.91% compared to control. It was concluded that the morphological growth and productivity of forage biomass increased with fertilizer rates and harvest ages. Treatment of 200 kg/ha urea and harvest age of 60 DAP produced the highest morphological and productivity.